2019
DOI: 10.1089/wound.2018.0790
|View full text |Cite
|
Sign up to set email alerts
|

Three Years' Experience of a Novel Biosynthetic Cellulose Dressing in Burns

Abstract: Objective: The use of porcine xenograft (PX) is widely spread in burn care. However, it may cause immunologic responses and other ethical and cultural considerations in different cultures. Therefore, there is a need for alternatives. The aim of this work is to test a novel biosynthetic cellulose dressing (Epiprotect ® ) on burn patients. Approach: Charts from 38 patients with superficial burns (SBs) ( n = 18) or excised burns ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Therefore, we do not know, if both dressings had an analgesic effect. Nevertheless, epicite hydro showed similar pain scores compared with SUPRATHEL, which is in accordance with results found in previous studies 7,8,32 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we do not know, if both dressings had an analgesic effect. Nevertheless, epicite hydro showed similar pain scores compared with SUPRATHEL, which is in accordance with results found in previous studies 7,8,32 …”
Section: Discussionsupporting
confidence: 92%
“…They treated 18 patients with superficial burn injuries with a mean TBSA of 8.2%. The median healing time was 28 days (13‐80 days), which is appreciably higher than the time for final closure in the epicite hydro treated wounds in the current study (16.1 days) 7 . Karlsson et al also reported patients who described that the cellulose got “stiff” over their joints 7 .…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…• Frequent dressing changes leading to increased length of stay/ outpatient visits • Increased cost • In some cases increased pain and stress to the patient. [2] To address these issues a literature review of EPIPROTECT was undertaken and there were common phenomenon's found; reduction in pain , reduced dressing changes and a decreased length in hospital stays [1,2,]. EPIPROTECT is also not associated with any ethical or cultural issues due to its biosynthetic nature [ 1,2 ] and has been proven to be cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…[2] To address these issues a literature review of EPIPROTECT was undertaken and there were common phenomenon's found; reduction in pain , reduced dressing changes and a decreased length in hospital stays [1,2,]. EPIPROTECT is also not associated with any ethical or cultural issues due to its biosynthetic nature [ 1,2 ] and has been proven to be cost effective. [3] For this case series we decided to target patients who had sustained superficial partial thickness burns with a focus on facial and hand injuries.…”
Section: Introductionmentioning
confidence: 99%